2016
DOI: 10.3329/sja.v14i1.29572
|View full text |Cite
|
Sign up to set email alerts
|

Infestation of sucking insect pests on five cotton cultivars and their impacts on varietal agronomic traits, biochemical contents, yield and quality

Abstract: The five cotton cultivars viz., CB1, CB3, CB5, CB8, and C12 were evaluated under field conditions to compare their resistance levels against the aphid species Aphis gossypii (Hemiptera: Aphididae) and the jassid species Amrasca devastans (Hemiptera: Cicadellidae). The effects of plant characteristics that could explain some of the varietal resistance levels were tested by measuring infestation levels, biochemical content, leaf trichome density, agronomic traits, yield, and quality of seed and fiber. In compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
1
8
1
Order By: Relevance
“…The variations of the growth stages, morphological structures like canopy, leaf hairs and trichomes of the bean species may impair the activity of the pest and predators. Amin et al (2016) reported that feeding efficiency, survival, growth and development of pest insects and their population abundance are affected by the morphological features and nutrient contents in host plants. Table 1 showed that weather parameters showed insignificant effect on the abundance of aphid on the bean species and the relationship was negatively…”
Section: Resultsmentioning
confidence: 99%
“…The variations of the growth stages, morphological structures like canopy, leaf hairs and trichomes of the bean species may impair the activity of the pest and predators. Amin et al (2016) reported that feeding efficiency, survival, growth and development of pest insects and their population abundance are affected by the morphological features and nutrient contents in host plants. Table 1 showed that weather parameters showed insignificant effect on the abundance of aphid on the bean species and the relationship was negatively…”
Section: Resultsmentioning
confidence: 99%
“…(Hemiptera: Cicadellidae). The results showed that the type of variety could influence the infestation level [50].…”
Section: Discussionmentioning
confidence: 98%
“…Sukhija et al (1987) found a yield loss of 9.74 q/ha due to the infestation of sucking insect pests in cotton. Amin et al (2016) observed significant differences in yield and quality attributes among the cotton varieties.…”
Section: Yield and Quality Attributesmentioning
confidence: 88%